Pregnant Mothers’ Knowledge, Attitude, and Practice Towards Prevention of Iron Deficiency Anemia in Georgia - Verulava, Tengiz; Gogua, Inga (AL-Kindy College Medical Journal, 2024)
Background: Anemia in pregnancy is a serious global health challenge, particularly affecting developing countries.Objectives: This study aimed to explore pregnant women's attitudes and perceptions regarding preventing iron deficiency anemia (IDA).Subjects and Methods: A qualitative research method was used to survey pregnant women with IDA and physicians through in-depth interviews.  The target sample consisted of 9 gynecologists and 26 pregnant women, selected through purposive sampling from three maternity hospitals in Tbilisi (Georgia).Results: The majority of pregnant women (n=22; 84.6%) had some knowledge about IDA and correctly identified its symptoms. However, despite high awareness, most lacked adequate knowledge about the causes and risk factors of IDA. While pregnant women were aware of healthy eating practices, they did not follow a proper diet. Obstacles to healthy eating included limited financial access to food as well as cultural and religious barriers. Although respondents had some knowledge about iron-rich foods, they were generally unaware of the need to take iron supplements for prevention. The majority of pregnant women (n=21; 80.8%) received little information about anemia from their family physicians, indicating a limited role of family doctors in IDA prevention during pregnancy.Conclusions: Although pregnant women possess knowledge and positive attitudes towards IDA prevention, their practices remain insufficient. The findings suggest a weak connection between knowledge of IDA prevention and healthy behavior, contributing significantly to anemia prevalence. To address this issue, it is essential to promote proper nutritional counseling for pregnant women during antenatal care, with a focus on strengthening family doctors' involvement. Additionally, awareness should be increased among women of reproductive age and adolescent girls.